1997
DOI: 10.1002/etc.5620161009
|View full text |Cite
|
Sign up to set email alerts
|

Trace metal exchange in solution by the fungicides Ziram and Maneb (dithiocarbamates) and subsequent uptake of lipophilic organic zinc, copper and lead complexes into phytoplankton cells

Abstract: The fungicides Ziram and Maneb (class dithiocarbamate) are organic Zn and Mn complexes in which the trace metal is chelated to organic dithiocarbamate ligands. The resulting organic metal complex is small, neutrally charged, and lipophilic in character. Short-term uptake experiments using a coastal diatom demonstrated that these lipophilic organic Zn and Mn complexes diffuse across the lipid bilayer that constitutes the plasma membrane. In addition, Cu 2ϩ and Pb 2ϩ ions in seawater solution undergo exchange re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 24 publications
1
21
0
2
Order By: Relevance
“…For example, whereas (CH 3 ) 2 their bioaccumulation by a marine alga (Thalassiosira weissflogii) is lower, presumably because elemental mercury and dimethylmercury do not readily form complexes with intracellular ligands. [12] Generally speaking, the observed uptake rates of lipophilic metal complexes are usually at least an order of magnitude higher than their hydrophilic metal counterparts, [10,11,16,17] which makes this mechanism potentially important for certain metals. Furthermore, uptake is sensitive to the pH of the medium, with a decreased bioaccumulation of the lipophilic metal complexes at low pH, potentially due to a reduction in the electrostatic repulsion between adjacent phospholipids, leading to their tighter packing and a decreased membrane permeability.…”
Section: Introductionmentioning
confidence: 99%
“…For example, whereas (CH 3 ) 2 their bioaccumulation by a marine alga (Thalassiosira weissflogii) is lower, presumably because elemental mercury and dimethylmercury do not readily form complexes with intracellular ligands. [12] Generally speaking, the observed uptake rates of lipophilic metal complexes are usually at least an order of magnitude higher than their hydrophilic metal counterparts, [10,11,16,17] which makes this mechanism potentially important for certain metals. Furthermore, uptake is sensitive to the pH of the medium, with a decreased bioaccumulation of the lipophilic metal complexes at low pH, potentially due to a reduction in the electrostatic repulsion between adjacent phospholipids, leading to their tighter packing and a decreased membrane permeability.…”
Section: Introductionmentioning
confidence: 99%
“…One likely route for the internalization of lipophilic metal complexes is the passive diffusion pathway. Phinney and Bruland [13,14] suggested that lipophilic organic metal (Cu, Cd, Pb) complexes could enter the coastal diatom Thalassiosira weiss‐flogii via direct passive diffusion. In addition, Croot et al [25] also demonstrated that the uptake of lipophilic complex Cu‐64‐oxine was by passive diffusion across the plasma membrane of five marine phytoplankton species.…”
Section: Resultsmentioning
confidence: 99%
“…All these ligands can bind with Cd and Zn to form hydrophilic ligand‐metal complexes with relatively low molecular weights (less than 500 Da). Previously, Phinney and Bruland [12,13] reported that lipophilic organic Zn, manganese, copper, and lead complexes could diffuse across the plasma membrane of marine diatoms. To determine whether lipophilic metal complexes are also bioavailable to Bacillus firmus and if they act as other possible metal uptake pathway, lipophilic ligands, 8‐hydroxyquinoline (Ox − ) and diethyldithiocarbamate (DDC) were used to complex with Cd and Zn to form small, neutrally charged, lipophilic organic ligand‐metal complexes in another uptake experiment.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrophobic metal complexes may directly diffuse through the cell membrane and thus may contribute to higher uptake fluxes of metals (Croot et al, 1999;Phinney and Bruland, 1997). Hydrophobic metal complexes may directly diffuse through the cell membrane and thus may contribute to higher uptake fluxes of metals (Croot et al, 1999;Phinney and Bruland, 1997).…”
Section: Metal Bioavailability To Algaementioning
confidence: 99%